TUBERCULUM SELLAE MENINGIOMA Vs. MACROADENOMA: How to differentiate preoperatively? - Mardjono,, I.; Arifin, M. Z.; Sidabutar, R.; Singh, and, A.; Sevline, E. O. (BALI MEDICAL JOURNAL, 2013)
Objective: Sellar region tumors may origin from a various number of structures and each of themhave a specific clinical and radiological appearance. Among these pathological processes, one of themost challenging is to distinguish between tuberculum sellae meningioma (TSM) and macroadenomahypophysis (MH). Differentiating these two entities preoperatively is very important to decide whichapproach will be most suitable and beneficial. The purpose of this study is to produce a simplepreoperative scoring system to differentiate these two that can be applied in specific conditions whereMRI is not available or could not be performed. Methods: This analytical retrospective cohort studycontains data obtained from patients treated in Neurosurgery Department of Dr. Hasan SadikinGeneral Hospital-Bandung from 1 January 2008 until 31 December 2010. There were 34 patientsenrolled in this study, in which 15 of them were diagnosed with MH and 19 patients diagnosed withTSM confirmed with pathology examination. Results: From clinical presentation we found that theevent of endocrinopathy occurs significantly in macroadenoma hypophysis (p=0.002). Whereas fromradiological evaluation there were 7 parameters that significantly distinguish these two entitiesincluding hyperostosis, sellar floor configuration, homogeneity of mass, contrast agent enhancement,waist configuration, peritumoral edema, and dural attachment. From these findings, we propose asimple scoring system to differentiate macroadenoma hypophysis and tuberculum sellae meningiomawith a 84.2% sensitivity and 100% specificity. Conclusion: although MRI is the modality of choice indifferentiating macroadenoma hypophysis and tuberculum sellae meningioma but our scoring systemcan be used as an aid in choosing best surgical approach.